Interpersonal communication patterns of Aisyiyah in cultural da'wah activities in isolated tribal communities - Rasyid, Erwin; Sugiantoro, Hari Akbar; Julijanti, Dinara Maya; Rosyidi, Moch Imron; Setiawan, Achdiar Redy (Jurnal Komunikasi, 2025)
This study aims to analyze the interpersonal communication patterns employed by PDA Banggai in their cultural dakwah activities directed at indigenous and isolated communities. The research adopts a case study approach. Data collected through in-depth interviews and document analysis. Data were thematically analyzed to identify PDA Banggai's interpersonal communication strategies. The findings indicate that PDA Banggai applies an adaptive form of interpersonal communication that emphasizes trust-building, the use of local languages, and collaboration with stakeholders. This approach is rooted in the values of Al-Ma’un, integrating religious messages with cultural contexts. The success of cultural dakwah hinges on context-sensitive interpersonal communication that respects local traditions. These findings offer insights into faith- and culture-based empowerment strategies among indigenous and marginalized communities